The Civil Law Aspects of Informed Consent to Medical Procedures - Chandra, Ade; Kurniawan, I Gede Agus (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Informed consent is a communication process between healthcare providers and patients regarding the medical procedures to be performed. Its aim is to provide sufficient information so that patients can make informed decisions, and it is regulated by various laws and regulations in Indonesia.Purpose of the Research: The purpose of this research is to analyze the legal position of informed consent from the perspective of Indonesian civil law and to examine the civil law implications that arise if there is a violation of the informed consent principle in medical procedures.Method of Research: This research uses normative legal methods with legislative and conceptual approaches, analyzing primary, secondary, and tertiary legal materials through literature study, and applying descriptive qualitative analysis.Results of Research: Research findings indicate that informed consent holds a strong legal position within the perspective of Indonesian civil law, being viewed as a manifestation of a therapeutic agreement that must meet the valid agreement requirements according to the Civil Code (KUHPerdata) and be supported by various regulations. Violations of the principles of informed consent can lead to significant civil legal implications, including claims for damages on the grounds of breach of contract or unlawful acts, cancellation of the therapeutic agreement, liability for breach of professional standards, and claims based on consumer protection law. These implications can involve healthcare professionals and healthcare institutions, with consequences that include payment of material and immaterial damages, the burden of proof in court, and impacts on reputation and medical practice.